The delaying effect of toripalimab on disease progression in patients with advanced hepatocellular carcinoma and changes in serum tumor markers - Zhuo Yin; Yaomin Xiao; Jiangxue Gu; Pei Hu; Jiandu Jing; Xia Wang; Yao Liu; Shirong Yan (World Journal of Surgical Oncology)
Abstract Objective This study aims to retrospectively analyze the delaying effect of toripalimab on disease progression in patients with advanced HCC and to evaluate its impact on serum tumor marker levels. Methods In this single-center retrospective study, 80 advanced HCC patients treated between January 2021 and January 2023 were divided into two groups: the intervention group (n = 40) receiving TACE plus toripalimab (240 mg every 3 weeks), and the control group (n = 40) receiving TACE alone. Primary endpoints included objective response rate (ORR) and overall survival (OS); secondary endpoints encompassed tumor marker dynamics, liver function parameters, T lymphocyte subsets, and safety. Results The intervention group exhibited significantly higher ORR compared to controls (70.0% vs. 35.0%, P = 0.002), with complete response (CR) in 25.0% of patients. Post-treatment tumor markers declined markedly in the intervention group: AFP (412.3 ± 98.5 to 156.7 ± 45.2 ng/mL, P < 0.001), HSP90α (68.4 ± 12.3 to 34.2 ± 8.7 ng/mL, P < 0.001), and CEA (15.2 ± 3.1 to 6.8 ± 1.9 ng/mL, P = 0.003). Liver function improved significantly (TBIL: 10.74 ± 1.14 vs. 15.47 ± 1.73 µmol/L; ALT: 24.97 ± 2.18 vs. 32.58 ± 2.25 U/L; both P < 0.001). The intervention group showed elevated CD4⁺ T cells (38.14 ± 2.69% vs. 32.56 ± 2.74%, P < 0.001) and CD4⁺/CD8⁺ ratio (1.38 ± 0.25 vs. 1.01 ± 0.33, P < 0.001). Adverse reactions were comparable (77.5% vs. 75.0%, P = 0.786), predominantly mild-to-moderate. After 2-year follow-up, median OS was significantly prolonged in the intervention group (20 vs. 16 months, P < 0.001), with a 77.5% survival rate versus 37.5% in controls (P < 0.001). Conclusion TACE combined with toripalimab demonstrates superior disease control in advanced HCC, marked by enhanced ORR, prolonged survival, reduced tumor biomarkers, improved liver function, and favorable immune modulation. The regimen exhibits acceptable safety, supporting its potential as a therapeutic option. Further prospective trials are needed to validate these findings and optimize combinatorial strategies.